The Effect of a Powered Lower-Body Exoskeleton on Physical and Cognitive Warfighter Performance. (September 2018) - Bequette, Blake; Norton, Adam; Jones, Eric; Stirling, Leia
This study analyzed the performance of twelve military members in a simulated, fatigue-inducing patrol task under three conditions: wearing a powered exoskeleton, wearing an unpowered exoskeleton, and without wearing an exoskeleton. While walking with weight at a prescribed pace over obstacles while following a confederate, participants were subject to a dual-task cognitive test in which they answered radio calls and visually scanned for lighted targets. Cognitive load was varied through a secondary radio task and measured with a visual reaction time test. Physical load and cognitive load were varied throughout the test. For this paper, the dependent measures of interest were reaction time for the visual task and lag time behind the confederate. Significant differences and interactions were found in the visual reaction time among the exoskeleton conditions, physical loads, and cognitive loads. Significant differences and interactions were also found for the lag time of the subject behind their prescribed pace, and the variability of this lag time. Both measures had significant interactions with subject. Future work should examine what design features of the exoskeleton and capability of the human are related to these variabilities. An understanding of subject variability can lead to improvements in integrated exoskeleton design.